Utilization of Natural Zeolite as Emission Filter in Catalytic Converter of Diesel Engine. Issue 1 (1st October 2022) - Hamid, Abdul; Wilujeng, Auliana Diah; Fatah, Misbakhul; Abdullah, Mohammad; Rohman, Ainur; Rohmah, Faizatur; Annafiyah
Abstract: The performance of natural zeolites in a catalytic converter to reduce the emission contents of diesel engine was studied in this research. Diesel engines are engines that use a high compression ratio to carry out a combustion process that will produce high contents of carbon monoxide (CO), nitrogen oxides (NOx ), and sulfur oxide (SO2 ) in diesel engine exhaust gases. One solution to reduce the contents of exhaust gas compounds in diesel engines is to use catalytic converter technology. In this study, the catalytic converter used natural zeolite as an emission filter. The catalytic converter was designed in the form of a pipe made from iron plates and hollow balls that were used as natural zeolite holders. A diesel engine emission test was conducted using a gas analyzer with engine speed variations. The results show the highest reduction efficiency in the emission contents of diesel engine (carbon monoxide (CO), nitrogen oxides (NOx ), and sulfur dioxide (SO2 )) of 46.14%, 22.77%, and 90.56%, respectively.